Epiphyseal osteosarcoma with serial changes of pretreatment imaging findings: a case report - Kotaro Watanabe; Hirokazu Shimizu; Tamotsu Soma; Ken Kuwahara; Hiroaki Hiraga; Norimasa Iwasaki; Masatake Matsuoka; Akira Iwata (World Journal of Surgical Oncology)
Abstract Background Osteosarcoma is not often at the forefront of differential diagnoses for epiphyseal bone tumors because of its rarity; however, more than half of individuals affected by these uncommon cases experience a delay in diagnosis. In such clinical situations, the decision to promptly perform a biopsy of an epiphyseal bone tumor—while considering a potential diagnosis of osteosarcoma —remains unclear, particularly in adolescents. We present herein a case of epiphyseal osteosarcoma in an adolescent, the diagnosis of which was made with minimal delay. Case presentation A 17-year-old male athlete presented to a previous hospital with knee pain. Radiographs obtained at the initial visit revealed a sclerotic mass in the femoral epiphysis. Computed tomography (CT) and magnetic resonance imaging (MRI) showed a 32-mm lesion adjacent to the remaining epiphyseal scar. When the patient was referred to our hospital 3 weeks later, X-rays showed a circular radiolucent shadow lesion, as well as an enlargement involving the scar on CT. MRI showed altered signal intensities in the cartilage region, with an increase in synovial fluid. These longitudinal changes indicated the need for an incisional biopsy with minimal delay, considering the possibility of malignancy, which resulted in a diagnosis of epiphyseal osteosarcoma. The patient received perioperative chemotherapy followed by a wide resection. The pathological examination of the resected sample validated the initial diagnosis. As of 1 year post-surgery, disease relapse had not been detected. Conclusions This case highlights the benefit of longitudinal imaging investigations, which assisted in making a crucial diagnosis with minimal delay and enabled timely initiation of treatment before further disease progression.